Controlled frequency breathing reduces inspiratory muscle fatigue - Burtch, A. R.; Ogle, B. T.; Sims, P. A.; Harms, C. A.; Symons, T. B.; Folz, R.J.; Zavorsky, G. S. (The Journal of Strength and Conditioning Research, 2017)
Controlled frequency breathing (CFB) is a common swim training modality involving holding one's breath for approximately 7-10 strokes before taking another breath. We sought to examine the effects of CFB training on reducing respiratory muscle fatigue. Competitive college swimmers were randomly divided into either the CFB group that breathed every 7-10 strokes or a control group that breathed every 3-4 strokes. Twenty swimmers completed the study. The training intervention included 5-6 weeks (16 sessions) of 12 × 50-m repetitions with breathing 8-10 breaths per 50-m (control group) or 2-3 breaths per 50-m (CFB group). Inspiratory muscle fatigue was defined as the decrease in maximal inspiratory pressure (MIP) between rest and 46 seconds after a 200-yard freestyle swimming race (115 seconds [SD 7]). Aerobic capacity, pulmonary diffusing capacity, and running economy were also measured pre- and posttraining. Pooled results demonstrated a 12% decrease in MIP at 46 seconds post-race (-15 [SD 14] cm H2O, effect size = -0.48, p < 0.01). After 4 weeks of training, only the CFB group prevented a decline in MIP values before to 46 seconds after race (-2 [13] cm H2O, p > 0.05). However, swimming performance, aerobic capacity, pulmonary diffusing capacity, and running economy did not improve (p > 0.05) posttraining in either group. In conclusion, CFB training appears to prevent inspiratory muscle fatigue; yet, no difference was found in performance outcomes.